Four years of Oddens’ Bookmarks: The Fascinating World of Maps and Mapping - Oddens, Roelof P. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
Not everyone will be interested in maps showing the distribution of various species of earthworms in North Dakota, especially as the design of these maps is not be very impressive either. Nevertheless, there is a link to such maps in Oddens’ Bookmarks. This is a Website that tries to provide as complete a coverage as possible of all Websites containing cartography. This paper is not attempting to show examples of Websites the bookmarks are linked to. Rather, it gives a short introduction to Oddens’ Bookmarks, referring to the history and development of the site, its contents, the problems I am faced with, and my views of its near future.